Hormontherapie in der Peri- und Postmenopause - Meyer, Sophie; Seifert-Klauss, Vanadin (DMW - Deutsche Medizinische Wochenschrift, 2018)
The recently published 18-year-follow-up of the WHI-study might resolve the long-standing dispute about hormone therapy, possibly reconciling the opposing parties attributing life-threatening risks to either the administration or the withholding of hormone therapy. 16 608 women without hysterectomy had taken either combined hormone therapy with estrogen and progestin or placebo for an average of 5.2 years, while 10 739 women after hysterectomy (and bilateral ovarectomy in 40 %) had taken either estrogen therapy alone or placebo for an average of 7 years. 7489 deaths were recorded until 2014. Over both studies, mortality was 27.1 % after hormone therapy and 27.6 % after placebo. New findings on perimenopause can help towards phase-adapted and complaint-targeted hormone therapy in the future.
Keywords: Perimenopause; Postmenopause; Hormontherapie; Östrogen; Gestagen